Efficient removal of arsenic from water using a granular adsorbent: Fe–Mn binary oxide impregnated chitosan bead. (October 2015) - Qi, Jianying; Zhang, Gaosheng; Li, Haining
Graphical abstract: The photograph of Fe–Mn binary oxide impregnated chitosan bead and adsorption isotherm of arsenic, which demonstrate rather high adsorption capacities for both arsenate and arsenite, especially the latter. Highlights: A novel sorbent of Fe–Mn binary oxide impregnated chitosan bead was fabricated. The granular sorbent is more effective for As(III) removal than As(V). The sorbent can be effectively regenerated and repeatedly used. The sorbent can be readily used in flow-through systems. Abstract: A novel sorbent of Fe–Mn binary oxide impregnated chitosan bead (FMCB) was fabricated through impregnating Fe–Mn binary oxide into chitosan matrix. The FMCB is sphere-like with a diameter of 1.6–1.8 mm, which is effective for both As(V) and As(III) sorption. The maximal sorption capacities are 39.1 and 54.2 mg/g, respectively, outperforming most of reported granular sorbents. The arsenic was mainly removed by adsorbing onto the Fe–Mn oxide component. The coexisting SO4 2−, HCO3 − and SiO3 2− have no great influence on arsenic sorption, whereas, the HPO4 2− shows negative effects. The arsenic-loaded FMCB could be effectively regenerated using NaOH solution and repeatedly used. In column tests, about 1500 and 3200 bed volumes of simulated groundwater containing 233 μg/L As(V) and As(III) were respectively treated before breakthrough. These results demonstrate the superiority of the FMCB in removing As(V) and As(III), indicating that it is a promising candidate for arsenic removal from real drinking water.